2023
DOI: 10.1002/aenm.202300249
|View full text |Cite
|
Sign up to set email alerts
|

Toward High Efficiency Water Processed Organic Photovoltaics: Controlling the Nanoparticle Morphology with Surface Energies

Abstract: Here efficient organic photovoltaic devices fabricated from water‐based colloidal dispersions with donor:acceptor composite nanoparticles achieving up to 9.98% power conversion efficiency (PCE) are reported. This high efficiency for water processed organic solar cells is attributed to morphology control by surface energy matching between the donor and the acceptor materials. Indeed, due to a low interfacial energy between donor and the acceptor, no large phase separation occurs during the nanoparticle formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In comparison to the Laval et al study, lower performances were achieved, mainly due to lower J SC and FF. This difference can be explained by the change in PTQ10 molar mass (60 kg mol −1 in Laval et al , 23 versus 110 kg mol −1 herein), resulting in lower intermolecular diffusion of Y6 in the PTQ10 domains. Nevertheless, the same thermal treatment (200 °C) was required to achieve the highest performances.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In comparison to the Laval et al study, lower performances were achieved, mainly due to lower J SC and FF. This difference can be explained by the change in PTQ10 molar mass (60 kg mol −1 in Laval et al , 23 versus 110 kg mol −1 herein), resulting in lower intermolecular diffusion of Y6 in the PTQ10 domains. Nevertheless, the same thermal treatment (200 °C) was required to achieve the highest performances.…”
Section: Resultsmentioning
confidence: 90%
“…For instance, Laval et al recently reported a record efficiency of 9.98% for miniemulsion-based solar cells using PTQ10 :Y6 NPs stabilized by SDS, with an optimized donor:acceptor morphology due to close interfacial energies. 23 A high annealing temperature of 200 °C was, however, required to achieve homogeneous film formation and optimum performance. Such a high thermal treatment can be detrimental for large-scale production, both for energy consumption and viability of flexible substrates used in roll-to-roll industrial manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…Soft X-ray microscopy is indeed becoming a more and more widespread analytical tool for investigating complex systems at the micrometric and sub-micrometric levels, especially when combined with X-ray spectroscopy capabilities. 15 Several synchrotrons worldwide have installed STXM beamlines, 16–25 similar to each other but at the same time each with unique capabilities. STXM is a scanning technique where the sample is usually raster-scanned across a micro- or nano-probe by photons delivered by suitable X-ray optics (Fig.…”
Section: Introductionmentioning
confidence: 99%